A user-centered approach to the evaluation of the aldult Chinese language lending collections in Singapore public libraries. - Tan, Woan Chyn. (2008)
This explorative and descriptive study aims to determine whether the adult Chinese lending collections in Singapore public libraries are meeting the information needs of the library users. This study uses the user-centred collection evaluation approach of circulation statistics analysis, library users' survey and the National Library Board (NLB) public libraries staff survey. The profile of the users, how they use the public libraries, the problems they had encountered in searching of the reading materials within the public libraries and their suggestions to improve the existing services were collected and analyzed in this study.